MENAKAR KETERLIBATAN KONGREGASI KATOLIK DALAM MENEGAKKAN KESETARAAN GENDER DI INDONESIA (STUDI KASUS VIVAT INTERNATIONAL – INDONESIA) (Jurnal Nawala Politika, 2022)
This study seeks to see the involvement of the Catholic Church in the feminism agenda through its congregations. Indeed, feminism has entered the body of the Catholic Church since the Vatican Council II. The council has produced documents that show concern for the position of women. VIVAT International – Indonesia, which was initiated by SVD, is a concrete form of the participation of the Catholic Church in the agenda of seeking gender equality. VIVAT International – Indonesia has succeeded in advocating and protecting victims of violence and trafficking in women. By using qualitative research methods, the author tries to narrate in detail the data obtained from the sources. Then, draw a common thread from the findings in the field with Rosemary Radford Ruether's feminist theology theory. VIVAT International – Indonesia as an extension of the Catholic Church has succeeded in reconstructing the concept of imago de'i; Humans are created equal in the likeness and image of God. However, this does not necessarily mean that the Catholic Church can be fully involved in the genderrelated agenda. This is because the Catholic Church collides with the patriarchal reality which is already inherent in the body of the church itself.